Microstructure and hydrogen storage properties of the Mg2−xYxNi0.9Co0.1 (x = 0, 0.2, 0.3, and 0.4) alloys - Li, Defa; Huang, Feng; Ren, Bingzhi; Wang, Shujie; Zhang, Wei; Zhu, Liming (Scientific reports, 2024)
Rare earth elements have excellent catalytic effects on improving hydrogen storage properties of the Mg 2 Ni-based alloys. This study used a small amount of Y to substitute Mg partially in Mg 2 Ni 0.9 Co 0.1 and characterized and discussed the effects of Y on the solidification and de-/hydrogenation behaviors. The Mg 2−x Y x Ni 0.9 Co 0.1 (x = 0, 0.2, 0.3, and 0.4) hydrogen storage alloys were prepared using a metallurgy method. The phase composition of the alloys was studied using X-ray diffraction (XRD). Additionally, their microstructure and chemical composition were studied using scanning electron microscopy and energy-dispersive X-ray spectroscopy, respectively. The hydrogen absorption and desorption properties of the alloys were studied using pressure-composition isotherms and differential scanning calorimetric (DSC) measurements. The structure of the as-cast Mg 2 Ni 0.9 Co 0.1 alloy was composed of the peritectic Mg 2 Ni, eutectic Mg–Mg 2 Ni, and a small amount of pre-precipitated Mg–Ni–Co ternary phases, and was converted into the Mg 2 NiH 4 , Mg 2 Ni 0.9 Co 0.1 H 4 , and MgH 2 phases after hydrogen absorption. Furthermore, the XRD patterns of the alloys showed the MgYNi 4 phase and a trace amount of the Y 2 O 3 phase along with the Mg and Mg 2 Ni phases after the addition of Y. After hydrogen absorption, the phase of the alloys was composed of the Mg 2 NiH 4 , MgH 2 , MgYNi 4 , YH 3 , Y 2 O 3 , and Mg 2 NiH 0.3 phases. With the increase of Y addition, the area ratios of the peritectic Mg 2 Ni matrix phase in the Mg 2−x Y x Ni 0.9 Co 0.1 (x = 0, 0.2, 0.3, and 0.4) alloys gradually decreased until they disappeared. However, the eutectic structure gradually increased, and the microstructures of the alloys were obviously refined. The addition of Y improves the activation performance of the alloys. The alloy only needed one cycle of de-/hydrogenation to complete the activation for x = 0.4. The DSC curves showed that the initial dehydrogenation temperatures of Mg 2 Ni 0.9 Co 0.1 and Mg 1.8 Y 0.2 Ni 0.9 Co 0.1 were 200 and 156 °C, respectively. The desorption activation energies of the hydrides of the Mg 2 Ni 0.9 Co 0.1 and Mg 1.8 Y 0.2 Ni 0.9 Co 0.1 alloys calculated using the Kissinger method were 94.7 and 56.5 kJ/mol, respectively. Moreover, the addition of Y reduced the initial desorption temperature of the alloys and improved their kinetic properties.